Unemployment, Reemployment, and Health Insurance Status Among Older Workers in the Flexible Labor Market. Issue 4 (4th July 2016) - Lippmann, Stephen; Brown, J. Scott
Abstract : As employment becomes more precarious, and spells of displacement become more common across the labor market, many individuals are forced to make decisions about the speed at which they seek reemployment and the types of employment they will seek. Using repeated cross‐sectional data from various years of the Displaced Worker Supplement of the Current Population Survey, we examine the degree to which employer‐provided health insurance and organizational provision of advanced layoff warning helped workers—particularly those from earlier birth cohorts—navigate the labor market during a period of growing employment flexibility. Our results indicate that workers from older cohorts, rather than older chronological ages, suffered more from displacement in terms of longer unemployment spells and declines in job quality upon reemployment. Workers able to obtain a job with health insurance had shorter unemployment durations, while those displaced from jobs with health insurance remained unemployed for longer periods of time. Advance notice appears to reduce some of the disproportionately negative effects of displacement for older workers, perhaps by easing the shock of a psychological contract breach. Our findings point to the importance of historical and cultural factors in shaping labor market outcomes.